Proceso de Atención de Enfermería en Neonato de 35 Semanas de Gestación con Gastrosquisis. - Jara Álvarez, Joel Steven (2022)
In this present case study, we apply nursing care to obtain excellent results with the patient diagnosed with Gastroschisis, for which she underwent surgery, this process takes consistency and permanence in the follow-up of the newborn. Gastroschisis is a congenital anomaly evidenced by umbilical protrusion of the right side of the stomach. This disease can be treated in pregnant women at week 14 of pregnancy with ultrasounds and complementary tests that are carried out in the medical control of the pregnant woman. But in my present clinical case, the mother did not have any medical control, the delivery was evidenced by pre-term spontaneous physiological delivery with the aforementioned diagnosis. The main tool for the management of the newborn diagnosed with Gastroschisis was the Nursing Care Process, where we obtained the expected results for the effective recovery of the patient. The clinical case was completed following the guidelines of the NANDA NIC and NOC taxonomy, which were very useful when understanding the disease and being able to carry out a quality care plan, obtaining good results with the recovery of the newborn.